2019
DOI: 10.1111/ijcp.13409
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility and economic burden of routine serum lipase determination in the Emergency Department

Abstract: Background Serum lipase is a rapid and reliable laboratory test central to diagnosing acute pancreatitis (AP). Routine use in the emergency department (ED) setting for all cases of abdominal pain or as part of a standard laboratory biochemical profile may lead to unnecessary expenses. Aim To examine the utility of serum lipase determination at a tertiary care centre ED. Methods Retrospective cross‐sectional study of ED patients having serum lipase determination over a 12‐month period. Electronic medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Despite the common use of amylase and lipase in patients presenting with abdominal pain, their clinical value was debated. Previous studies have shown an association between AC and GC,11–13 however, an increase in their serum levels may be confounded by accompanying pancreatitis. Our results and the results of other studies did not show a significant association between these biomarkers and GC.…”
Section: Discussionmentioning
confidence: 94%
“…Despite the common use of amylase and lipase in patients presenting with abdominal pain, their clinical value was debated. Previous studies have shown an association between AC and GC,11–13 however, an increase in their serum levels may be confounded by accompanying pancreatitis. Our results and the results of other studies did not show a significant association between these biomarkers and GC.…”
Section: Discussionmentioning
confidence: 94%
“…Although CT can detect early pancreatitis with a sensitivity of 60-95%, measurement of blood pancreatic enzyme, which detects pancreatitis with a sensitivity of 96.6% and specificity of 99.4%, was not performed at the admission [ 7 , 8 ]. The appropriateness of routine blood testing of lipase as a screening tool for acute pancreatitis in the emergency room remains unestablished [ 9 ]. Even if he had developed pancreatitis undetectable by CT upon arrival at the emergency room, according to Ranson's criteria, he did not meet any of the risk factors except for the unknown blood glucose level [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The article by El Halabi et al highlights the economic burden of test over-utilisation. 1 Inclusion of non-routine tests in laboratory test panels and inconsistent adherence to clinical guidelines leads to unnecessary testing in patients where no benefit is gained. It is often considered 'safer', for both the requester and patient, to request the test than not.…”
Section: No Abdominal Pain No Lipasementioning
confidence: 99%